Principles of subsidiary application of the law - Фасій, Богдан Володимирович; Фасий, Богдан Владимирович; Fasiy, Bohdan V. (My University, 2015)
The article examines the principles of application of the subsidiary legislation to the civil and contiguous relationships. In this study focuses on the following principles of subsidiary application of the law: the principle of inadmissibility of arbitrary interference in private life; the principle of freedom of contract; the principle of judicial protection of rights and interests; the principles the rule of law, legality, equality; the principles of fairness, honesty, reasonableness.

У статті досліджується принципи субсидіарного застосування норм законодавства до цивільних та суміжних з ним відносин. В даному дослідженні зосереджено увагу на такі принципи субсидіарного застосування норм законодавства як: принцип неприпустимості довільного втручання у сферу приватного життя; принцип свободи договорів; принцип судового захисту прав та інтересів; принципи верховенства права, законності, рівності, обґрунтованості; принцип справедливості, добросовісності, розумності.

В статье исследуются принципы субсидиарного применения норм законодательства к гражданским и смежным с ними отношением. В данном исследовании сосредоточено внимание на таких принципах субсидиарного применения норм законодательства как: принцип недопустимости произвольного вмешательства в сферу частной жизни; принцип свободы договоров; принцип судебной защиты прав и интересов; принципы верховенства права, законности, равенства, обоснованности; принцип справедливости, добросовестности, разумности.
Fasiy B. V. Principles of subsidiary application of the law / B. V. Fasiy // Часопис цивілістики. – 2015. – Вип. 19. – С. 113-116.
Keywords: civil law; principles; legal gaps; subsidiary application; legislative technique; related areas of law; цивільне законодавство; принципи; прогалина в праві; субсидіарне застосування; законодавча техніка; суміжні галузі права; гражданское законодательство; принципы; пробел в праве; субсидиарное применение; законодательная техника; смежные отрасли права